2009
DOI: 10.1634/theoncologist.2008-0178
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Gastric MALT Lymphoma: Is It a Truly Localized Disease?

Abstract: Section editor George P. Canellos has disclosed no financial relationships relevant to the content of this article.The content of this article has been reviewed by independent peer reviewers to ensure that it is balanced, objective, and free from commercial bias. Target audience:Physicians who wish to advance their current knowledge of clinical cancer medicine in lymphoma oncology. LEARNING OBJECTIVESAfter completing this course, the reader should be able to:1. In your patients with gastric MALT lymphoma (GML)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…25,26 To exclude this possibility in the current series, a subset of 34 cases of the present cohort were subjected to upper gastrointestinal (GI) endoscopy. All cases but one had no endoscopic or histopathological evidence of lymphoma; 21/33 cases were found with gastritis, and among them 10 were HP positive; 5 cases received HP eradication treatment and were HP negative with normal GI endoscopy on reevaluation.…”
Section: In Very Rare Cases Mz-like Lymphocytosis Can Be the Presentmentioning
confidence: 99%
“…25,26 To exclude this possibility in the current series, a subset of 34 cases of the present cohort were subjected to upper gastrointestinal (GI) endoscopy. All cases but one had no endoscopic or histopathological evidence of lymphoma; 21/33 cases were found with gastritis, and among them 10 were HP positive; 5 cases received HP eradication treatment and were HP negative with normal GI endoscopy on reevaluation.…”
Section: In Very Rare Cases Mz-like Lymphocytosis Can Be the Presentmentioning
confidence: 99%
“…Although Raderer reported that non‐gastric MALT lymphomas are significantly more prone to disseminated disease as compared with gastric MALT lymphomas, our data showed no difference between gastric and intestinal tract lymphomas (36.7% in gastric vs 30% in intestine, P = 0.575). The variations in distributions could be due to the different types of examinations and more stringent classification criteria used in different studies, since more thorough examination could lead to more precise staging …”
Section: Discussionmentioning
confidence: 99%
“…a and b). Considering the partial overlap with the biological profiles reported as characteristic of the various types of well‐recognized MZLs, as well as the clinical evolution patterns, we proposed that CBL‐MZ may represent: (i) the leukaemic manifestation of a pre‐existing undiagnosed lymphoma, a notion supported by anecdotal reports that MZ‐like lymphocytosis can be the presenting feature of occult gastric MALT lymphoma ; (ii) the early stage of a lymphoma with a finite chance of clinical progression; (iii) the precursor of a lymphoma, especially SMZL/SLLU, requiring additional oncogenic hits for disease progression ; (iv) a stable clonal disorder with little or no risk of evolution to lymphoma; or (v) a heterogeneous group of disorders of potential MZ origin but also unrelated entities (e.g. lymphoplasmacytic lymphoma) with overlapping features at presentation.…”
Section: Marginal Zone Lymphomasmentioning
confidence: 96%